Edukasi Audio Visual Tentang Self Management pada Pasien Hipertensi - Shanty Chloranyta; Rusmala Dewi; Sinta Wijayanti (Universitas Malahayati Lampung, 2023)
ABSTRACT Blood pressure above 140 mm Hg systolic and above 90 mm Hg diastolic is defined as hypertension. Individuals with cardiovascular disease are advised to take care of themselves or manage themselves (self-management) in everyday life as part of disease management. The aim of the study was to limit knowledge before and after audio visual self-management counseling in hypertensive patients in the working area of the Way Kandis Health Center. This study used a quantitative method, using a pre-test and post-test, with 30 respondents as subjects. Data collection used the Hypertension Self-Management Behavioral Questionnaire (HSMBQ). The results of the paired t-test for self-management knowledge tests before and after on hypertensive patients in the Way Kandis Health Center office showed p-value = 0.000. The conclusion from this study, audio-visual education conducted on hypertensive patients about self-management, there is a difference between pre-post education so that it is hoped that nurses can modify education using audiovisual methods to increase the interest of individuals with hypertension in an effort to increase knowledge about self-management in hypertension. Keywords: Audiovisual, Education, Hypertension, Self Management ABSTRAK Tekanan darah dengan sistolik di atas 140 mm Hg dan diastolik di atas 90 mm Hg dinyatakan sebagai hipertensi. Individu dengan penyakit kardiovaskular dianjurkan mengatur diri sendiri (self management) dalam kehidupan sehari-hari sebagai bagian dari manajemen penyakit. Tujuan penelitian yakni membandingkan pengetahuan sebelum dan sesudah edukasi audio visual self management pada pasien hipertensi di wilayah kerja Puskesmas Way Kandis. Penelitian ini menggunakan metode kuantitatif, menggunakan uji pre-test dan post-test, subjek 30 responden. Pengumpulan data menggunakan hypertension self management behavioural questionnaire (HSMBQ). Hasil uji t-test berpasangan untuk tes pengetahuan manajemen diri sebelum dan sesudah pada pasien hipertensi di ruang kerja Puskesmas Way Kandis menunjukkan p-value = 0,000. Kesimpulan dari penelitian ini, edukasi audio visual yang dilakukan pada pasien hipertensi tentang tentang self management, terdapat perbedaan antara pre-post edukasi sehingga diharapkan perawat dapat melakukan modifikasi edukasi dengan menggunakan metode audiovisual untuk meningkatkan minat individu dengan hipertensi dalam upaya meningkatkan pengetahuan tentang self management pada hipertensi. Kata Kunci : Audiovisual, Edukasi, Hipertensi, Self Management